GENDER AND VOICE IN MUSIC: : A REVIEW OF THE TRANSGENDER PERSON AND THE MALE-FEMALE BINARISM IN SINGING PRACTICE - Carlos de Menezes, Valter; Gabriell Fernandes Cruz, Lucas (Revista Gênero e Interdisciplinaridade, 2022)
The voice is something intrinsic to identity and represents our entire history, marked by diverse experiences, by the space we grew up in, and the culture that surrounds us. These factors contribute to our construction as an individual, and the voice is the door through which we affirm our own identity. For the transgender person, their voice reaffirms their truth, their identity. This study aims to understand gender, to perceive the relationship between voice and identity, and to recognize gender in the music space, specifically in the practice of singing, a vocal activity which uses the voice that is often stereotyped by ideals of male-female binarism.